2018
DOI: 10.1002/anie.201712011
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Tellurophene‐Based Acceptors for Organic Solar Cells

Abstract: Triplet materials have been employed to achieve high-performing organic solar cells (OSCs) by extending the exciton lifetime and diffusion distances, while the triplet non-fullerene acceptor materials have never been reported for bulk heterojunction OSCs. Herein, for the first time, three triplet molecular acceptors based on tellurophene with different degrees of ring fusing were designed and synthesized for OSCs. Significantly, these molecules have long exciton lifetime and diffusion lengths, leading to effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(83 citation statements)
references
References 60 publications
(120 reference statements)
1
81
0
1
Order By: Relevance
“…During charge migration, nongeminate (NG) or bimolecular recombination may occur; [ 6,7 ] this leads to the formation of CT excitons, with either singlet ( S CT) or triplet ( T CT) character in a 1:3 ratio following the spin statistics. [ 8 ] These nearly energetically degenerate S CT and T CT excitons will recombine or separate again into FC. The recombination of S CT to the ground state (S0) can be effectively suppressed because of the high enough S CT energy ( E CT ), according to the energy‐gap law (Figure S1a, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…During charge migration, nongeminate (NG) or bimolecular recombination may occur; [ 6,7 ] this leads to the formation of CT excitons, with either singlet ( S CT) or triplet ( T CT) character in a 1:3 ratio following the spin statistics. [ 8 ] These nearly energetically degenerate S CT and T CT excitons will recombine or separate again into FC. The recombination of S CT to the ground state (S0) can be effectively suppressed because of the high enough S CT energy ( E CT ), according to the energy‐gap law (Figure S1a, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…[26] The tellurophene-based molecule S15c showed the maximum field-effect hole mobility of 1.8 cm 2 V À 1 s À 1 , demonstrating the great potential for OFET applications. [29] The transient photoluminescence spectra showed S17, S18, and S19 possessed different lifetime of 2.9 ms, 11.6 ms, and 24.4 ms, respectively, suggesting the efficient intersystem crossing due to the large spin orbital coupling. [27] It was observed that the optical bandgap narrowed down from DPP2T(BTh) 2 (S16a) to DPP2T (BSe) 2 (S16b) to DPP2T(BTe) 2 (S16c).…”
Section: Applications Of Tellurophene-based Small Moleculesmentioning
confidence: 93%
“…The first triplet tellurophene-PDI based acceptor (BFPTP) possessed long exciton lifetime and diffusion distances for efficient exciton dissociation rather than recombination. Thus, the PBDB-T: BFPTP blended films delivered a PCE of 7.52% (Yang et al, 2018a ). A fused and twisted PDI derivative with twisted thieno[2,3-b]thiophene (TT) as linker (cis-PBI) was reported.…”
Section: Pdi Based Small Molecule Electron Acceptorsmentioning
confidence: 99%